Design of campus network terminal positioning system based on topology discovery - YU Bo; HU Donghui; TANG Linchun (Tongxin xuebao)
At present, there was not an effective approach to position network terminal in the campus network management. An algorithm of network topology discovery was proposed, which could discover all the layer-2 and layer-3 network devices and their connections. Based on the proposed algorithm, the approach was proposed and carried out with program design, which could position campus network terminal fast, using the SNMP protocol and database. Theoretical analysis and practical application indicate that the algorithm of topology discovery is simple and efficient, and the terminal positioning system is fast and accuracy.